Desain Kreatif Lingkungan Bermain Luar Ruangan: Sebuah Solusi Bagi Heterogenitas Karakteristik Anak Usia Dini - Ningsih, Ade Cahya; Fauzi, Fauzi (PAKAR Pendidikan, 2023)
Early childhood outdoor play environments should be designed as creatively as possible to be accessible to all children with diverse individual characteristics. Many models of children’s outdoor play environments designed in schools do not seem to fully consider the diverse characteristics of children, including special needs, cultural diversity, and differences in children’s physical and cognitive abilities, so children cannot make the most of the play environment. This research aims to reveal the creative design of outdoor play environments that early childhood can access and utilize. The author uses a descriptive qualitative approach with a literature study research type. Documentation was conducted to collect data by collecting records from books or articles that correlate with the research topic. The data analysis process is carried out by taking several stages, namely, (1) describing the characteristics of early childhood, (2) describing the nature of the outdoor play environment, (3) analyzing the relevance of the nature of the outdoor play environment to the characteristics of early childhood, and (4) synthesizing the criteria for the creative design of early childhood outdoor play environments. The results revealed that the creative design of early childhood outdoor play environments has several criteria, namely (1) focusing on meeting children’s needs, (2) flexibility of play equipment, (3) paying attention to children’s safety, and (4) providing a feeling of pleasure for children. Every school should own these four criteria to encourage collaboration, creativity, and cognitive stimulation of children in the utilization of the play environment.